2009
DOI: 10.1021/ol9002509
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective C−H Bond Activation: Ligand and Solvent Free Iron-Catalyzed Oxidative C−C Cross-Coupling of Tertiary Amines with Terminal Alkynes. Reaction Scope and Mechanism

Abstract: FeCl 2 catalyzes the oxidative C-C cross-coupling of tertiary amines with terminal alkynes into propargylamines using (t-BuO) 2 as oxidant. The reaction can be applied to aromatic and aliphatic amines and alkynes without solvent. High chemoselectivity for aminomethyl groups is due to a steric factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(53 citation statements)
references
References 65 publications
(38 reference statements)
1
49
0
3
Order By: Relevance
“…In this regard, transition-metal-catalyzed C H bond activation, particularly of unactivated sp 3 C H bonds, has emerged to be a promising but highly challenging approach in organic synthesis [12][13][14][15]. Recently, the direct oxidative cyanation of C H bonds in tertiary amines to give corresponding ␣-aminonitriles has attracted much interest as these compounds are highly useful and versatile intermediates which find extensive applications in a wide range of natural products and nitrogen containing bioactive compounds such as alkaloids [16][17][18][19]. Further, these bi-functional organic compounds having adjacent functional groups show dual reactivity as the nucleophilic addition provides an easy access to various compounds such as ␣-amino aldehydes, ketones and ␤-amino alcohols [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, transition-metal-catalyzed C H bond activation, particularly of unactivated sp 3 C H bonds, has emerged to be a promising but highly challenging approach in organic synthesis [12][13][14][15]. Recently, the direct oxidative cyanation of C H bonds in tertiary amines to give corresponding ␣-aminonitriles has attracted much interest as these compounds are highly useful and versatile intermediates which find extensive applications in a wide range of natural products and nitrogen containing bioactive compounds such as alkaloids [16][17][18][19]. Further, these bi-functional organic compounds having adjacent functional groups show dual reactivity as the nucleophilic addition provides an easy access to various compounds such as ␣-amino aldehydes, ketones and ␤-amino alcohols [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, Volla and Vogel reported iron-catalyzed CDC reactions of tertiary amines and terminal alkynes to give propargylamines (Scheme 32) [58]. Screening reactions revealed that FeCl 2 without solvent in air was the best catalyst.…”
Section: -Csp Cdc Reactionmentioning
confidence: 99%
“…Instead of 1,3-dicarbonyl systems, an α-sp 3 C-H bond from nitrogen was found effective in CDC with terminal alkynes (Scheme 79) (99).…”
Section: The Cdc Between Sp 3 and Sp C-h Bondsmentioning
confidence: 99%